Effect of steady-state methadone on high fructose corn syrup consumption in rats. (February 2018) - Daniels, Stephen; Pratt, Mick; Zhou, Yan; Leri, Francesco
Patients undergoing methadone maintenance treatment self-report enhanced preferences for, and excessive consumption of, foods rich in sugar. However, it is unclear whether these are direct pharmacological effects of methadone or the consequences of metabolic dysfunctions induced by addiction to illicit opiates. Hence, the current study in drug-naïve male Sprague-Dawley rats explored the effects of steady-state methadone delivered by osmotic mini-pumps (13 days; 0, 10, 30 mg/kg/day) on consumption of rat chow and a palatable, sweet, liquid high fructose corn syrup solution. Six days after the removal of the pumps, mRNA expression of genes involved in responses to stress and rewards were quantified: pro-opiomelanocortin in the hypothalamus, mu-opioid receptor in the nucleus accumbens, and dopamine D2 receptor in the dorsal striatum. Taste reactivity and locomotion tests were also performed throughout the study. It was found that methadone increased caloric intake from high fructose corn syrup and reduced caloric intake from chow, effects that could not be directly ascribed to changes in high fructose corn syrup taste reactivity or motor functions. However, the changes in caloric intake displayed significant tolerance, and mRNA expression analysis suggested that methadone attenuated the effect of high fructose corn syrup on pro-opiomelanocortin mRNA, and possibly on dopamine D2 receptor mRNA. These findings in rats suggest that the pharmacological effect of methadone, administered to achieve steady-state maintenance, may not be the primary cause of dietary alterations reported by patients maintained on methadone.